Perinuclear anti neutrophil cytoplasmic antibody vasculitis with nonspecific muscle pain - Dihingia, Prasanta; ., Harikishore; Jha, Anshu Kumar (International Journal of Research in Medical Sciences, 2020)
This is a case report describing p-ANCA vasculitis presenting with nonspecific muscle pain. It is a very uncommon finding seen in p-ANCA vasculitis patients which they usually present with palpable purpura alone. In this case, along with nonspecific muscle pain, renal involvement of the disease has been explained and there are no upper and lower respiratory tract complaints which favours more towards microscopic polyangitis.